A new autoinflammatory and autoimmune syndrome associated with NLRP1 mutations: NAIAD (NLRP1-associated autoinflammation with arthritis and dyskeratosis). Issue 7 (13th December 2016) - Grandemange, Sylvie; Sanchez, Elodie; Louis-Plence, Pascale; Tran Mau-Them, Frédéric; Bessis, Didier; Coubes, Christine; Frouin, Eric; Seyger, Marieke; Girard, Manon; Puechberty, Jacques; Costes, Valérie; Rodière, Michel; et al.
Abstract : Objectives: Inflammasomes are multiprotein complexes that sense pathogens and trigger biological mechanisms to control infection. Nucleotide-binding oligomerisation domain-like receptor (NLR) containing a PYRIN domain 1 (NLRP1), NLRP3 and NLRC4 plays a key role in this innate immune system by directly assembling in inflammasomes and regulating inflammation. Mutations in NLRP3 and NLRC4 are linked to hereditary autoinflammatory diseases, whereas polymorphisms in NLRP1 are associated with autoimmune disorders such as vitiligo and rheumatoid arthritis. Whether human NLRP1 mutation is associated with autoinflammation remains to be determined. Methods: To search for novel genes involved in systemic juvenile idiopathic arthritis, we performed homozygosity mapping and exome sequencing to identify causative genes. Immunoassays were performed with blood samples from patients. Results: We identified a novel disease in three patients from two unrelated families presenting diffuse skin dyskeratosis, autoinflammation, autoimmunity, arthritis and high transitional B-cell level. Molecular screening revealed a non-synonymous homozygous mutation in NLRP1 (c.2176C>T; p.Arg726Trp) in two cousins born of related parents originating from Algeria and a de novo heterozygous mutation (c.3641C>G, p.Pro1214Arg) in a girl of Dutch origin. The three patients showed elevated systemic levels of caspase-1 and interleukin 18, which suggested involvement of NLRP1 inflammasome. Conclusions: We demonstrate the responsibility of human NLRP1 in a novel autoinflammatory disorder that we propose to call NAIAD for NLRP1- associated autoinflammation with arthritis and dyskeratosis. This disease could be a novel autoimmuno-inflammatory disease combining autoinflammatory and autoimmune features. Our data, combined with that in the literature, highlight the pleomorphic role of NLRP1 in inflammation and immunity. Trial registration number: NCT02067962 ; Results.